2022
DOI: 10.3389/fenvs.2022.916916
|View full text |Cite
|
Sign up to set email alerts
|

Chemometric Optimization of Solid-Phase Extraction Followed by Liquid Chromatography-Tandem Mass Spectrometry and Probabilistic Risk Assessment of Ultraviolet Filters in an Urban Recreational Lake

Abstract: Solid-phase extraction (SPE) of eleven ultraviolet filters (UVFs): benzophenone-1 (BP-1); benzophenone-3 (BP-3); benzophenone-4 (BP-4); isoamyl p-methoxycinnamate (IAMC), homosalate (HMS); 4-hydroxybenzophenone (4-HB); 4-methylbenzylidene camphor (4-MBC); octocrylene (OC); octyl dimethyl-p-aminobenzoate (OD-PABA); 2-ethylhexyl-4-methoxycinnamate (EHMC); and avobenzone (AVO), has been optimized using Plackett-Burman design, Box-Behnken design, and Derrindzer desirability function. Of the six SPE variables studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…EHMC was also reported as the most common organic UV filter in cosmetics (Chaiyabutr et al, 2021). Also, a study on the occurrence of 11 UVFs in an urban recreational lake in the same city where the studied sunscreen products were purchased revealed EHMC to have the highest concentrations of all UVFs in water (Lukić et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EHMC was also reported as the most common organic UV filter in cosmetics (Chaiyabutr et al, 2021). Also, a study on the occurrence of 11 UVFs in an urban recreational lake in the same city where the studied sunscreen products were purchased revealed EHMC to have the highest concentrations of all UVFs in water (Lukić et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that potential health hazards and risks from UVFs in sunscreen PCPs are based mainly on the direct dermal exposure route (Raslan et al, 2020). However, different UVFs contribute vastly differently to potential health risks (Luki c et al, 2022). In addition, the combined risk depends on the concentration of different UVFs in sunscreens and human exposure.…”
mentioning
confidence: 99%
“…The desirability function [ 32 ] was used to find the optimal conditions of the examined factors to define the optimal quality levels for different responses. The desirability function is a quick transformation of different responses to one objective function [ 33 ]. The desirability function has two steps: (1) transformation of every individual response to an individual desirability function ( d i ) that ranges from 0 to 1 ( d i = 0 undesirable response; d i = 1 desirable response) and (2) calculating of overall desirability ( D ) by taking the geometric average of all individual desirability values (Equation (1)).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, after a comparison of the pressurized liquid extraction with Soxhlet and ultrasound-assisted methods, the recoveries were proved to be better with the pressurized liquid extraction (90.6–107.8%) compared with 83.5–88.7% and 81.4–85.2% for the other two methods, respectively [ 71 ]. Another SPE method using Oasis cartridges packed with 100 mg HLB sorbent was proposed by Luki et al to preconcentrate and detect four BPs [ 72 ]. The working parameters were optimized by an experimental design which revealed that the elution solvent and percentage of methanol and pH were the influencing factors.…”
Section: Sample Preparation For Benzophenone Detectionmentioning
confidence: 99%